Christianity, Empire, and the Making of Religion in Late Antiquity - Schott, Jeremy M. (Divinations, 2008)
Main description: In Christianity, Empire, and the Making of Religion in Late Antiquity, Jeremy M. Schott examines the ways in which conflicts between Christian and pagan intellectuals over religious, ethnic, and cultural identity contributed to the transformation of Roman imperial rhetoric and ideology in the early fourth century C.E.